National emissions reported to the Convention on Long-range Transboundary Air Pollution (LRTAP Convention), v1.0, 2025 ... - European Environment Agency (European Environment Agency, 2025)
This metadata refer to the data on emissions of air pollutants submitted to the LRTAP Convention and copied to EEA. Data compiled are annual national total and sectoral emissions of air pollutants and associated activity data reported by EEA member and cooperating countries. Data are available for download in the UNECE/EMEP Nomenclature for Reporting (NFR19) format used by countries. A consolidated dataset for all countries in the NFR19 format and consistent with the European Union's air pollutant emission inventory submission to the LRTAP Convention is also provided. ...